Dispersive liquid–liquid microextraction coupled with graphite furnace atomic absorption spectrometry for determination of trace cobalt in environmental water samples. Issue 8 (20th June 2020) - Han, Quan; Huo, Yanyan; Yang, Xiaohui; He, Yaping; Wu, Jiangyan
ABSTRACT: A highly sensitive, simple and rapid method was developed for the determination of ultra-trace cobalt by dispersive liquid-liquid microextraction (DLLME) combined with graphite furnace atomic absorption spectrometry (GFAAS). The combination of DLLME and GFAAS methods is favourable for GFAAS is a well-established technique with excellent sensitivity, and is suitable for low volume of sample of the remained phase obtained after DLLME. For DLLME, a newly synthesised reagent 5-(5-Cyano-2-pyridylazo)-2, 4-diaminotoluene (5-CN-PADAT) was used as a chelating agent, 1, 2-dichloroethane (CH2 ClCH2 Cl) and acetonitrile (CH3 CN) as extraction and dispersive solvent. Several variables potentially affecting the extraction efficiency and its subsequent determination, such as type and volume of extraction and disperser solvents, pH of test solution, extraction time, volume and concentration of the chelating agent and salt effect, were investigated and optimised. After phase separation, 10 µL of the sedimented phase containing enriched analytes was injected into GFAAS for the determination of cobalt. Under the optimised conditions, the analytical graph was linear in the range of 0.04 1.0 ng mL −1, and the limit of detection was 0.01 ng L −1 for cobalt. The relative standard deviation (RSD) for 10 replicate measurements of 0.2 ng L −1 of cobalt was 3.6%. Enrichment factor (EF) calculated as the ratio of the slopes of the calibration graphs obtained with and without DLLME was 96 for 5.0 mL sample solution. The method was successfully applied to the determination of trace cobalt in water samples with satisfactory results.